The effect of cladoceran, Daphnia magna, on the growth and pupation of Aedes aegypti L. mosquito larvae - Ankita Thakur; Devinder Kaur Kocher (Journal of Basic and Applied Zoology, 2022)
Abstract Background Dengue and chikungunya are two mosquito-borne viruses transmitted by the mosquito, Aedes aegypti, and are responsible for great public health concerns in India. The present study tested the effect of Daphnia magna, a freshwater cladoceran, on the growth and pupation of Ae. aegypti larvae. Results Ae. aegypti third instar larvae and adult, D. magna, were introduced in the ratios 1:1, 1:2 and 1:3 into beakers and placed in an illuminated BOD incubator at a temperature of 26 ± 1 °C. The delay in the duration of larval stages (the time taken from third instar stage until their emergence as adults) was measured. The emergence of adults was delayed for 3–4 days in the treatments where the ratio of D. magna was thrice the number of Ae. aegypti larvae. The L3 larval stage was found to be more prone to mortality than later instars, with 51.66% larval mortality. The sex ratio of males to females emerged was only 5:5 in the 1:3 ratio. Body size of both males and females was significantly reduced in all the treatment sets in the ratios: 1:1, 1:2 and 1:3 when compared with the control set. Longevity of adult was also reduced from 8–15 to 4–7 days in the case of males, and in the case of females it was reduced from 14–25 to 5–9 days in the treatment set when Daphnia was introduced thrice the number of Aedes larvae. Conclusions Our study provides evidence that D. magna affects the growth and pupation of Aedes larvae and consequentially the life history parameters that affect the fitness of the population.